Implementation of an Optical Character Reader (OCR) for Bengali language - Chowdhury, Muhammed Tawfiq; Islam, Md. Saiful; Bipul, Baijed Hossain; Rhaman, Md. Khalilur (© 2016 Institute of Electrical and Electronics Engineers Inc., 2017)
This conference paper was presented in the International Conference on Data and Software Engineering, ICODSE 2015; Universitas Gadjah MadaYogyakarta; Indonesia; 25 November 2015 through 26 November 2015 [© 2015 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICODSE.2015.7436984